Historical training course of Mathematic teacher training north Minas Gerais (1960-1990) - Almeida, Shirley; Gomes, Maria (Educação, Escola & Sociedade, 2019)
The work presented here results from a doctoral research, whose objective was to investigate the history of the formation of mathematics teachers in the north of Minas Gerais, in the degree course of the current State University of Montes Claros (Unimontes). The focused period extends from the 1960s to the 1990s. We use the methodology of Oral History, according to the parameters of GHOEM — Oral History and Mathematical Education Group, integrating the project developed by it to map the formation and performance of teachers of Mathematics in Brazil. We believe that our production can provide subsidies for the understanding of the process of formation of Mathematics teachers in the north of Minas Gerais and join efforts for the construction of the History of Education in the State and in Brazil. Keywords: History of Mathematics Education. Teacher training. Mathematics.